Development of a self-care program satisfaction questionnaire for cardiovascular patients in Iran - Mehdi Nosratabadi; Zohreh Halvaiepour (Journal of Cardiovascular and Thoracic Research, 2018)
Introduction: Evaluating patient satisfaction with self-care program can increase the likelihood of complying with treatment. There is no valid and reliable tool to be used in measuring Iranian patient’s satisfaction with self-care program. So, this study intends to develop the patient satisfaction questionnaire in the context of cardiac rehabilitation and test its validity and reliability in Iranian patients. Methods: A cross-sectional study was conducted to develop and validate the patient satisfaction with self-care program questionnaire using structural modeling. A total of 155 cardiovascular patients referring to cardiovascular rehabilitation center in Isfahan were participated in this study. Construct and criterion validity, and test-retest reliability were used to validate the scale. Results: After reviewing literature and receiving expert’ comments for items pooling as well as conducting exploratory factor analysis, 10 statements in the model remained which are loaded on 2 factors. These 2 subscales explained about 63 percent of variance of all constructs. The Cronbach’s alpha coefficient ranged between 0.87 and 0.89 for the whole questionnaires and its subscales. Besides, scale had excellent stability (intraclass correlation = 0.86). Criterion validity analyzed through correlational analyses revealed significant relationships between the current scale and Patient Satisfaction Questionnaire Short Form (PSQ11). CFA revealed an acceptable overall fit for two-factor model. Conclusion: The scale integrated 10 items in two dimension including patient satisfaction with rehabilitation program and patient satisfaction with personnel of rehabilitation team. In total, most of the psychometric properties of the 10-item patient satisfaction with self-care program scale achieved the standard level and were sufficient to recommend for cardiac rehabilitation settings.